Early socioeconomic circumstances and adverse childhood experiences in 10-year-old children - Peres, FS (2019)
Background Evidence showed that adverse childhood experiences (ACEs) are associated with the development of disease later in life and premature death. Examining the occurrence of these experiences at early ages would contribute to intervene and therefore to reduce health inequalities. This study aimed to assess the prevalence of ACEs among 10-year-children and to examine its association with early socioeconomic circumstances. Methods At the fourth wave of the population-based birth cohort Generation XXI, from Porto, Portugal, 5153 children completed a self-report questionnaire on 9 experiences related to household dysfunction and physical and emotional abuse. Socioeconomic circumstances included household income, maternal and paternal education, and history of parental unemployment. Logistic regression was performed to calculate the Odds Ratios (OR) and 95% Confidence Intervals (95%CI). Results A high prevalence of physical and emotional abuse was reported by children from low socioeconomic circumstances. A graded relationship between socioeconomic circumstances and cumulative ACEs was observed, for instance, low household income was associated with increased number of ACEs (one event [OR = 1.10; 95%CI: 0.89-1.36], two events [OR = 1.41; 95%CI: 1.15-1.73], three events [OR = 1.67; 95%CI: 1.34-2.06], and four or more events [OR = 2.05; 95%CI: 1.64-2.55]). Also, living with one parent or none of them increased the likelihood of reporting multiple ACEs (OR = 5.50; 95%CI: 4.23-7.13). Conclusions Children from low socioeconomic circumstances were more likely to report multiple adverse experiences in the first decade of life. These findings support that children from less advantaged environments might be at a higher risk of co-occurrence of adverse experiences during their childhood.